Pistas de uma professora preceptora para o desenvolvimento da prática de licenciandos na iniciação à docência - Ramos, Daiana Aparecida (2021)
This study is the result of a professional master's research, linked to the Graduate Program in Science and Mathematics Teaching at the Federal University of Uberlândia, which aimed to investigate, through narratives, reflections on the teaching practice of my experience as Teach-er-Trainer when receiving the resident licentiate students of the degree course in physics at the federal university of Uberlândia participating in the pedagogical residency project (RP). The residency enables collaborative actions between higher education and basic education teach-ers, inserting the licentiate in the field of work, stimulating the articulation between theory and practice in undergraduate courses. As a methodological approach, this study used narra-tive research, as in the narrative analysis of narratives, the researcher plays the role of consti-tuting meanings to the narrators' experiences through the search for unifying and particular elements, assuming that, through this procedure, they would be unveiling the authentic way of individual life. It can be said that this work was just the beginning of a long journey, with several scales that allowed the opening of a curtain on an immense stage that will present great interaction shows between resident teacher, preceptor teacher, coordinating teacher and school community